Impact of Enforcement and Co-Management Activity on Compliance Behavior of Fishermen in Peninsular Malaysia - Jamal, Ali (2004)

(untitled)
Economic models of regulatory compliance in fisheries usually assume the decision to comply or to violate fisheries regulations depends primarily on expected monetary costs and benefits. Enforcement agencies tend, as a result, to focus only on increasing probability of detection and penalty severity as a tool to control violations. However, increasing the quantity of monitoring activities and improving the quality of these activities may prove to be very costly; while raising probability of detection and fines, it may not be the best strategy. Enforcement agencies have tried to develop innovative approaches in order to improve fishery resources and induce compliance with fishery regulations without necessarily engaging a larger amount of (scarce) resources to achieve this objective. To this extent, co-management activities have become an important policy tool. The purpose of this thesis was to examine the factors affecting compliance behavior with regard to zoning regulation among trawler, purse seine and drift net fishermen in thirteen fishing areas of Peninsular Malaysia. Frequent violations of regulation will impact on the demand for protection, and therefore lead to greater expenditure on law enforcement. Policy makers who want to improve compliance face two choices: the first choice is whether to focus only on building staff capacity to detect and correct non-compliance, or the second choice a combination of strategies building staff capacity and at the same time building commitment among fishermen so that they will comply with regulations. Logit econometric model was used to estimate the dichotomous violation decision of 284 Peninsular Malaysia fishermen. Data from the surveyed fishermen showed that, besides probability of detection and penalty severity, factors such as illegal gain, fishing areas and co-management activities could also influence compliance behavior. The results of the empirical analysis provided evidence of the relationship between deterrence and co-management strategies on the one hand, and compliance on the other. These findings imply that co-management activities should be strengthened to complement the deterrence strategies in the management of fishery resources in Peninsular Malaysia.